If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = -1x + 264 Reorder the terms: 7 = 264 + -1x Solving 7 = 264 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7 + x = 264 + -1x + x Combine like terms: -1x + x = 0 7 + x = 264 + 0 7 + x = 264 Add '-7' to each side of the equation. 7 + -7 + x = 264 + -7 Combine like terms: 7 + -7 = 0 0 + x = 264 + -7 x = 264 + -7 Combine like terms: 264 + -7 = 257 x = 257 Simplifying x = 257
| y+51=89 | | -37-8= | | h(t)=-16t^2+20t+17 | | x(x+3)-5=3x+20 | | 3x+7-5(x+1)=2x+5 | | 5y+3y-5=6(4y+3) | | -4s+9=-24 | | 2r+4=-16 | | (6+9)x=15x | | 10z^2+17z-20= | | 8y-12y+9=24-y | | 120-x=3x | | 3(r+1)-1[2(3-2r)-3(3-r)]=2(r+5)-4 | | 120+.40x=50+.60x | | 1/2x-5x | | 120x+.40=50x+.60 | | 5(2m+3)-1(1-2m)=2[3(3+2m)-1(3-m)] | | 2x(50-15)=2y | | 16vw^2x^3-28v^4w^4= | | 4(x+9)-6(9x-5)=14 | | y-9=25 | | 9(3x+6)=-x(x-2) | | 2[5(w+3)-1(w+1)]=3(1+w) | | (4/9x)/(2/3x) | | 1x+3+2x=-8 | | 4k^2-7k=2 | | 2(n+7)=8-n | | 1-4(x+5)=7x-8 | | 4.5=0.5x | | 9q^2-17q=2 | | 2.46=4/3(3.14)r^3 | | -3m-11+16m=15 |